2021
DOI: 10.1002/dc.24816
|View full text |Cite
|
Sign up to set email alerts
|

Increased gene expression of TIMP1 and CHI3L1 in fine‐needle aspiration biopsy samples from papillary thyroid cancer as compared to benign nodules

Abstract: Background Thyroid nodules are common ultrasound findings with malignancy rate 7%–15%. Our objective was to assess the relative expression of the tissue inhibitor of metalloproteinase‐1 gene (TIMP1) and chitinase‐3‐like protein 1 gene (CHI3L1) in fine‐needle aspiration biopsy (FNAB) washouts and the serum levels of their protein products (TIMP‐1 and chitinase‐3‐like protein 1 known as YKL‐40) in patients with papillary thyroid cancer (PTC) and patients with benign nodules. Furthermore, the correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Previous studies have demonstrated that CHI3L1 is highly expressed in PTC compared with adjacent normal tissues ( 29 , 30 ), and it was further identified that CHI3L1 is significantly upregulated in RR-DTC compared with PTC in the present study. These findings suggest that CHI3L1 may serve an important role in thyroid cancer and could be associated with the dedifferentiation of tumor cells in RR-DTC.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have demonstrated that CHI3L1 is highly expressed in PTC compared with adjacent normal tissues ( 29 , 30 ), and it was further identified that CHI3L1 is significantly upregulated in RR-DTC compared with PTC in the present study. These findings suggest that CHI3L1 may serve an important role in thyroid cancer and could be associated with the dedifferentiation of tumor cells in RR-DTC.…”
Section: Discussionsupporting
confidence: 76%
“… 28 Several studies found that the serum levels of TIMP1 are higher in the patients with DTC compared to the patients with benign nodule. 33 , 34 However, we did not evaluate the serum levels of TIMP1 of TC patients in the present study. Growing evidence suggests TIMP1 impacts on various cellular processes and regulates the initiation and progression in a wide range of cancers.…”
Section: Discussionmentioning
confidence: 81%